Improved stability in P3HT:PCBM photovoltaics by incorporation of well‐designed polythiophene/graphene compositions. Issue 9 (4th May 2020) - Yuan, Qingshan; Zhang, Zunju; Li, Lei; Agbolaghi, Samira; Mousavi, Saina
Abstract: Morphological and photovoltaic stabilities of poly(3‐hexylthiophene) (P3HT):phenyl‐C61 ‐butyric acid methyl ester (PC71 BM) solar cells were investigated in pristine and modified states. To this end, four types of patterned/assembled nanostructures, namely reduced graphene oxide (rGO)‐ g ‐poly(3‐dodecylthiophene)/P3HT patched‐like pattern, rGO–polythiophene/P3HT/PC71 BM nanofiber, rGO‐ g ‐P3HT/P3HT cake‐like pattern and supra(polyaniline (PANI)‐ g ‐rGO/P3HT), were designed on the basis of rGO and various conjugated polymers. Intermediately covered rGO nanosheets by P3HT crystals (supra(PANI‐ g ‐rGO/P3HT)) performed better than sparsely (patched‐like pattern) and fully (cake‐like pattern) covered ones in P3HT:PC71 BM solar cell systems. Supra(PANI‐ g ‐rGO/P3HT) nanohybrids largely phase‐separated in active layers (root mean square = 0.88 nm) and also led to the highest performance (power conversion efficiency of 5.74%). The photovoltaic characteristics demonstrated decreasing trends during air aging for all devices, but with distinct slopes. The steepest decreasing plots were obtained for the unmodified P3HT:PC71 BM devices (from 1.77% to 0.28%). The two supramolecules with the most ordered structures, that is, cake‐like pattern (10.12 mA cm −2, 51%, 0.58 V, 2.2 × 10 −6 cm 2 V −1  s −1, 4.3 × 10 −5 cm 2 V −1  s −1, 0.69 nm and 2.99%) and supra(PANI‐ g ‐rGO/P3HT) (12.51 mA cm −2, 57%, 0.63 V, 1.2 × 10 −5 cm 2 V −1  s −1, 3.4 × 10 −4 cm 2 V −1  s −1, 0.82 nm and 4.49%), strongly retained morphological and photovoltaic stabilities in P3HT:PC71 BM devices after 1 month of air aging. According to the morphological, optical, photovoltaic and electrochemical results, the supra(PANI‐ g ‐rGO/P3HT) nanohybrid was the best candidate for stabilizing P3HT:PC71 BM solar cells. © 2020 Society of Chemical Industry Abstract : Morphological and photovoltaic stabilities of P3HT:PC71 BM solar cells were increased with the incorporation of predesigned nanohybrids.